PENGGUNAAN MODEL THINK TALK WRITE (TTW) UNTUK MENINGKATKAN KETERAMPILAN MENULIS TEKS NARASI PADA SISWA KELAS IV SD NEGERI 02 TALAMAU PASAMAN BARAT - Sisri Wahyuni; Sukma, Elfia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was motivated by the low narrative writing skills of fourth-grade students at SD Negeri 02 Talamau, caused by the dominance of lecture methods, lack of student engagement, and minimal teacher guidance. The aim of this study is to improve narrative writing skills through the Think Talk Write (TTW) learning model. The method used is classroom action research (CAR) with a qualitative and quantitative approach. The research subjects consisted of teachers as observers and fourth-grade students as participants. The study was conducted in two cycles, each including planning, implementation, observation, and reflection stages. Data were collected through observation, interviews, documentation, and learning outcome tests, then analyzed descriptively. The results showed that implementing the TTW model had a positive impact on students' narrative writing skills. The lesson planning score increased from 87% (B) in the first cycle to 98% (SB) in the second cycle. Teacher and student activity also improved, from 91.06% (SB) to 96.42% (SB). The average writing skill score increased from 72.74 (C) to 88.83 (B), while knowledge scores rose from 75.86 (C) to 90.43 (SB). Thus, the TTW model has been proven effective in enhancing the narrative writing skills of fourth-grade students at SD Negeri 02 Talamau.